Sie sind auf Seite 1von 2

# NOTES ON MSE QUESTION 2809448

√ Pn−1 nk 1 1
Abstract. We show that 2πne−n k=0 k! n−k ∼ 2
log(n)

Let’s define an = cn αn with cn = 2πne−n and

n−1
X nk 1
αn =
k! n − k
k=0
We first proof two lemmas which, properly combined, directly yield the answer to
OPs question
Lemma 0.1.
∞ n
nn e−t nn
Z  
t
αn = dt = 1+ In −1
n!
0 t n! n

## Proof. This follows straightforwardly from the identity (n−k)! n 1


R ∞ n−k−1 −t n! k = k! together with
(n − k − 1)! = 0 t e and a final application of the Binomial theorem. 

Lemma 0.2.
1
In ∼ log(n)
2
Proof. Let us choose a δ such that 1  δ  n (there are further restrictions on
the size of δ but something like C log(n) is certainly good enough). We split the
integral at this value and examine the resulting expression one after another:
Z δ
In,< ∼ e−t = 1 − e−δ ∼ 1 = o(log(n))
0
t n

since 1 + n ∼ 1 + t in this range. On the other hand
∞ ∞
e−t e−tn
Z Z
In,> ∼ (1 + t/n)n = (1 + t)n
δ t δ/n t
t n

since 1 + n  1 in this range. Furthermore it is pretty clear (singularity +
exponential decay) that this integral is dominated by it’s behaviour at the origin.
This means that can further approximate

∞ 2 ∞ 2
e−nt /2
e−t
Z Z
1
In,> ∼ = √ ∼ log(n) + o(log(n))
δ/n t δ/ 2n t |{z} 2
IbP
Putting everything together this means that

1
In = In,> + In,< ∼ log(n) + o(log(n))
2

1
2 NOTES ON MSE QUESTION 2809448

Theorem 0.3.
1
an ∼ log(n)
2

Proof. From Stirling’s approximation we get that nn /n! ∼ en / 2πn so by Lemma
1 and 2
en 1
an ∼ cn √ In ∼ log(n)
2πn 2
